Analysis of Single Nucleotide Polymorphism in Fim H Gene from Uropathogenic E.coli - Sabreen Fleih Neno Al-Fatlawi1, Laith Abdul Hassan M. Jwaid2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Urinary tract infection is defined as presence of microbial pathogens in the urinary tract withassociated symptoms. The infection affects both lower and upper urinary tracts and is known as acute cystitisand polynephritis respectively. This study done to detect the variation of single nucleotide in FimH gene andits correlation with the pathogenicity of uropathogenic Escherichia coli caused the urinary tract infection.Materials and Methods: The study group included 150 patients with Urinary tract infection. There were120 (80%) female and 30 female (20%) their age ranges between (5-55) years, seen in Al-Hussein TeachingHospital for the period from January 2019 to March 2019. The dominant form (48.39%) of patients withurinary tract infection caused by UPEC was found in the age group of 24-39 years old. Urine sampleswere collected from the patients. Bacterial isolation was identified by microscopic examination and culturecharacteristic on selective media MacConky agar, Eosin Methylene Blue and Chrome agar. Then the isolatedwere diagnosis by Vitek®2 system.Results: Bacteriological results showed that 62(41.3%) isolates were characterized as Escherichia coli.Genomic DNA was extracted from the bacterial culture for further molecular study to reveal C640T andT591A fimH gene Polymorphism. Polymerase chain reaction-restriction fragment length polymorphism(PCR-RFLP) technique was used for this purpose and digestion of the amplified DNA products byScarFI1390I and BsrI endonuclease respectively gave fragments with different molecular sizes whichexpress certain genotypes. This study detected that the prevalence rate of single nucleotide polymorphismC640T FimH was (85.48%), endonuclease enzyme only affects the C allele sequence and it does not haveany influence on the T allele sequence. The prevalence rate of single nucleotide polymorphism T591AfimH gene was (80.64%), endonuclease enzyme only affects the T allele sequence and it does not have anyinfluence on the A allele sequence.The result show only 62 isolates (41.3%) were given typical morphological characteristics and biochemicaltests related to E. coli, while the rest 88 isolates (58.6%) belonged to pathogenic bacteria from differentgenera.